Competitive Pasture Species to Suppress the Growth of Annual Riceflower (Pimelea trichostachya Lindl.) at Different Planting Densities and Spatial Arrangements - Rashid Saleem; Ali Bajwa; Shane Campbell; Mary T. Fletcher; Sundaravelpandian Kalaipandian; Steve W. Adkins (Plants)
This study assessed the effectiveness of four competitive pasture species—Premier digit grass (Digitaria eriantha Steud. var. Premier), Rhodes grass (Chloris gayana Kunth.), sabi grass (Urochloa mosambicensis Hack.), and buffel grass (Pennisetum ciliare L.) against the toxic annual riceflower (Pimelea trichostachya Lindl.) at varying planting densities and ratios. At six plants pot−1, with a 66:33 grass-to-weed ratio, riceflower biomass decreased by 73.7%, 82.5%, 73.7%, and 60.6% when grown alongside Premier digit, Rhodes, sabi, and buffel grasses, respectively. Similarly, with four plants pot−1 at a 75:25 ratio, reductions were 69.1%, 79.8%, 71.0%, and 44.5%, respectively. Annual riceflower experienced the greatest suppression when grown with Rhodes grass, showing aggressivity index (AI) values of −60.2 and −67.2 and relative crowding coefficient (RCC) values of 0.4 for both six and four plants pot−1. Premier digit grass also suppressed riceflower effectively, with riceflower AI values of −35.6 and −36.7 and RCC values of 0.5 and 0.6. Buffel grass had the least impact, with riceflower AI values of −41.1 and −27.9 and RCC values of 0.9 and 2.0. Sabi grass also demonstrated good suppressive effects, though slightly less than the top two species. Higher planting densities generally resulted in stronger riceflower suppression. The results highlight the importance of considering planting density, arrangement, and key plant traits when selecting pasture species for successful weed control. Based on these findings, we conclude that Premier digit grass and Rhodes grass show promising potential for effective suppression of annual riceflower growth.